Clinical usefulness of 2-deoxy-2-[18F] fluoro-d-glucose-positron emission tomography/computed tomography for assessing early oral squamous cell carcinoma (cT1-2N0M0). (28th April 2018) - Yamaga, Emi; Toriihara, Akira; Nakamura, Shin; Asai, Sakurako; Fujioka, Tomoyuki; Yoshimura, Ryoichi; Michi, Yasuyuki; Harada, Hiroyuki; Tateishi, Ukihide
Abstract : Although 2-deoxy-2-[ 18 F] fluoro-d -glucose-positron emission tomography/computed tomography has limitation for detecting cervical nodal metastases and synchronous cancers, it is a potentially prognostic indicator in early oral squamous cell carcinoma. Abstract: Background: Positron emission tomography with 2-deoxy-2-[ 18 F] fluoro-d -glucose integrated with computed tomography (FDG-PET/CT) is a useful method to evaluate patients with oral squamous cell carcinoma (OSCC). However, the prognostic significance of FDG-PET/CT for assessing early OSCC remains unclear. Methods: Pretreatment FDG-PET/CT of 205 consecutive patients (125 men, 80 women, mean age 59.7 year old) with early OSCC (cT1-2N0M0) between June 2010 and December 2014 were retrospectively analyzed. FDG avidity in primary lesions was assessed by visual interpretation. Thereafter, maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were measured in primary lesions. The relationship between each parameter and recurrence free survival (RFS) was assessed using the log-rank test. The performance of FDG-PET/CT for diagnosing metastatic lesions and synchronous cancer was also assessed. Results: During the follow-up period (mean 32.9 months), 43 patients developed recurrences (21.0%). Patients with visually positive FDG uptake in primary lesions showed significantly shorter RFS than the others (63.0 months vs. 52.9 months, P = 0.005). In those patients, greater SUVmax, MTV, and TLG did not significantly predict shorter RFS. The sensitivity and specificity of FDG-PET/CT for cervical nodal metastases detection were 32.3% and 77.6%, respectively. FDG-PET/CT detected eight synchronous cancers (3.9%) and overlooked six synchronous cancers (2.9%). Conclusions: Although its utility for detecting cervical nodal metastases and synchronous cancers is limited, FDG-PET/CT is a potentially prognostic indicator in early OSCC.